Quantitative Local Probing of Polarization with Application on HfO2‐Based Thin Films. Issue 11 (7th October 2021) - Kwon, Owoong; Kang, Seunghun; Jo, Sanghyun; Kim, Yun Do; Han, Hee; Park, Yeehyun; Lu, Xiaoli; Lee, Woo; Heo, Jinseong; Alexe, Marin; Kim, Yunseok
Abstract: Owing to their switchable spontaneous polarization, ferroelectric materials have been applied in various fields, such as information technologies, actuators, and sensors. In the last decade, as the characteristic sizes of both devices and materials have decreased significantly below the nanoscale, the development of appropriate characterization tools became essential. Recently, a technique based on conductive atomic force microscopy (AFM), called AFM‐positive‐up‐negative‐down (PUND), is employed for the direct measurement of ferroelectric polarization under the AFM tip. However, the main limitation of AFM‐PUND is the low frequency (i.e., on the order of a few hertz) that is used to initiate ferroelectric hysteresis. A significantly higher frequency is required to increase the signal‐to‐noise ratio and the measurement efficiency. In this study, a novel method based on high‐frequency AFM‐PUND using continuous waveform and simultaneous signal acquisition of the switching current is presented, in which polarization–voltage hysteresis loops are obtained on a high‐polarization BiFeO3 nanocapacitor at frequencies up to 100 kHz. The proposed method is comprehensively evaluated by measuring nanoscale polarization values of the emerging ferroelectric Hf0.5 Zr0.5 O2 under the AFM tip. Abstract : Evaluation of a small polarization value at the nanoscale level is challenging because of the low signal‐to‐noise ratio. Herein, a polarization–voltage hysteresis loop with a high signal‐to‐noise ratio achieved via high‐frequency atomic force microscopy‐positive‐up‐negative‐down (AFM‐PUND) and application of a noise reduction method is demonstrated. In addition, the AFM‐PUND measurement on promising ferroelectric Hf0.5 Zr0.5 O2 is showing its applicability to ultra‐thin ferroelectrics.